Biopsy diagnosis of type 1 autoimmune pancreatitis: Does it bring a conclusion or confusion?. Issue 1 (7th December 2021) - Notohara, Kenji
Abstract: A biopsy‐based diagnosis of type 1 autoimmune pancreatitis (AIP) is now feasible via an endoscopic ultrasound‐guided fine‐needle biopsy, but there are potential issues to address. The benefits of acquiring large tissue samples include more successful immunostaining for Immunoglobulin G4 and more identifications of storiform fibrosis, obliterative phlebitis, and the ductal lesions of type 1 AIP. However, storiform fibrosis may not be present in all the type 1 AIP lesions. An interobserver agreement study revealed only slight‐to‐moderate agreement among pathologists diagnosing the histological findings of type 1 AIP. Potential reasons for disagreement are the different time phases of the inflammation (which result in heterogeneous histological pictures), a focal appearance of the typical histological findings, and the different definitions used by pathologists. We have thus devised guidance for diagnosing type 1 AIP based on biopsy tissues. In this guidance, we define each histological finding of type 1 AIP, for example, storiform fibrosis as a swirling arrangement of inflammatory cells, spindle‐shaped cells, and delicate collagens as a unit. The necessity of elastic stains for identifying obliterative phlebitis is explained, with examples of mimickers. Another important purpose of a biopsy in type 1 AIP cases is differentiation from pancreatic ductal adenocarcinoma (PDAC). In this situation, acinar‐ductal metaplasia observed in type 1 AIP is a mimicker of PDAC and should not be confused. For the resolution of potential disagreements among pathologists, a multi‐disciplinary approach with the collaboration of clinicians, radiologists, and pathologists is necessary to avoid confusion.